2010
DOI: 10.2466/pr0.106.1.54-64
|View full text |Cite
|
Sign up to set email alerts
|

Achievement, Attributions, Self-Efficacy, and Goal Setting by Accounting Undergraduates

Abstract: Correlations were examined between two measures of accounting self-efficacy achievement goal setting, attributions, and scores on the Accounting Practice Achievement Test, obtained 1 yr. apart for 124 freshmen in junior college. Analysis indicated favorable attribution contributed to a higher mean score on accounting self-efficacy. Students with higher perceived self-efficacy performed better on the proficiency tests. Those with higher self-efficacy also set higher goals for subsequent achievement tests. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 33 publications
3
26
0
2
Order By: Relevance
“…In addition, a study found that students with high achievement goals and high self-efficacy performed better than their counterparts (Cheng and Chiou, 2010). These findings refer to Bandura's (1986) social cognitive theory, which states that attainable goals, self-motivation, and controllable outcomes are crucial for self-efficacy and personal development.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, a study found that students with high achievement goals and high self-efficacy performed better than their counterparts (Cheng and Chiou, 2010). These findings refer to Bandura's (1986) social cognitive theory, which states that attainable goals, self-motivation, and controllable outcomes are crucial for self-efficacy and personal development.…”
Section: Introductionmentioning
confidence: 93%
“…Even when considering ability level and previous training on a lab task, high selfefficacy was strongly related to setting a high task goal among college undergraduates (Lock, Frederick, Lee, & Bobko, 1984). Similar results have been seen in separate college samples, with self-efficacy sharing a strong, positive relationship with the level of personal goals set (Cheng & Chiou, 2010;Gibbons & Weingart, 2001). People with high self-efficacy also voluntarily choose challenging rather than simple tasks.…”
supporting
confidence: 77%
“…These relationships explain additional variance above and beyond the relationship between performances across categories, attributed to general cognitive ability (Paunonen & Hong, 2010). Self-efficacy has also been found to be positively associated with performance on standardized accounting exams (Cheng & Chiou, 2010).…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 95%